The Effectiveness of the Translation Method Assisted by Interactive E-Whiteboard Media on the Mastery of Nahwī Structure in Writing Skills Among Seventh-Grade Students at MTs Darul Ulum Waru Sidoarjo - Rojulul Baqiyatus Soleh; Ida Miftakhul Jannah; Abdul Halim (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This research addresses the gap between traditional grammar instruction, which often leads to student boredom and low syntactic mastery, and the need for interactive, applied language practice. This study aimed to measure the effectiveness of integrating the Translation Method with Interactive E-Whiteboard Media on enhancing the mastery of tarkīb nahwī in writing skills among seventh-grade students at MTs Darul Ulum Waru Sidoarjo. Utilizing a quantitative quasi-experimental design with a Non-Equivalent Control Group, the sample consisted of 60 students (30 experimental, 30 control). Data were collected using a validated tarkīb nahwī test, focusing on mubtada’ mu’akhkhar and khabar muqaddam, and analyzed using the Independent Sample T-test and Two-way ANOVA. The results showed a highly significant difference in post-test scores (t=-19.012, Sig. 0.000), confirming the substantive effectiveness of the E-Whiteboard method. This improvement is attributed to dynamic visualization and real-time feedback, which accelerate the cognitive integration of form and meaning. This study contributes a transformative teaching model for Arabic grammar and recommends its adoption by teachers, while suggesting future research use mixed-methods and longitudinal designs on more complex syntax patterns.   Keywords: Interactive E-Whiteboard, Translation Method, Tarkīb Nahwī, Writing Skills